2009
DOI: 10.1161/circresaha.108.184051
|View full text |Cite
|
Sign up to set email alerts
|

The Ca V 3.2 T-Type Ca 2+ Channel Is Required for Pressure Overload–Induced Cardiac Hypertrophy in Mice

Abstract: Abstract-Voltage-gated T-type Ca 2ϩ channels (T-channels) are normally expressed during embryonic development in ventricular myocytes but are undetectable in adult ventricular myocytes. Interestingly, T-channels are reexpressed in hypertrophied or failing hearts. It is unclear whether T-channels play a role in the pathogenesis of cardiomyopathy and what the mechanism might be. Here we show that the ␣ 1H voltage-gated T-type Ca 2ϩ channel (Ca v 3.2) is involved in the pathogenesis of cardiac hypertrophy via the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
124
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(132 citation statements)
references
References 51 publications
7
124
1
Order By: Relevance
“…Ca V 3.2 is also preferentially expressed in fetal ventricles, but less so in adult ventricles, and therefore the T-type Ca 21 current is very small or even undetectable in adult ventricular myocytes (Perez-Reyes 2003;Chiang et al 2009). ACMs from both day-1 (Figures 6A-6C) and aged ( Figures 6D-6F) hearts also expressed Ca V 3.2 predominantly in the intracellular space rather than the cell periphery, whereas very weak signals were detected near the plasma membrane in adult cardiac ventricular myocytes ( Figures 6G-6I).…”
Section: Expression Of Fetal Cardiac Gene Products Anp and Ca V 32 Imentioning
confidence: 99%
“…Ca V 3.2 is also preferentially expressed in fetal ventricles, but less so in adult ventricles, and therefore the T-type Ca 21 current is very small or even undetectable in adult ventricular myocytes (Perez-Reyes 2003;Chiang et al 2009). ACMs from both day-1 (Figures 6A-6C) and aged ( Figures 6D-6F) hearts also expressed Ca V 3.2 predominantly in the intracellular space rather than the cell periphery, whereas very weak signals were detected near the plasma membrane in adult cardiac ventricular myocytes ( Figures 6G-6I).…”
Section: Expression Of Fetal Cardiac Gene Products Anp and Ca V 32 Imentioning
confidence: 99%
“…23 It has been recently reported that CaV3.2 (Cacna1h) is required for cardiac hypertrophy induced by pressure overload. 24 Likewise, crossbreeding of dnNRSF mice with transgenic mice lacking the target genes of REST/NRSF might provide a clue.…”
Section: Study Limitationsmentioning
confidence: 99%
“…However, Ca V 3.1 and Ca V 3.2 channels are also expressed in the heart where they are involved in pacemaking in the sinoatrial node (Ca V 3.1; 43 ) as well as in ventricular hypertrophy where Ca V 3.1 and Ca V 3.2 channels seem to play opposite roles. 44,45 Moreover, in resistance vessels Ca V 3.1 and Ca V 3.2 T-type channel protein expression has been demonstrated by immunolocalization to VSMCs 46-51 as well as ECs. 48,49,51,52 Interestingly, in human cerebral arteries the T-type isoforms expressed are the Ca V 3.2 and Ca V 3.3 channels, with no expression of Ca V 3.1 channels.…”
mentioning
confidence: 99%